Functional extracellular matrix hydrogel modified with MSC‐derived small extracellular vesicles for chronic wound healing. Issue 4 (14th February 2022) - Ma, Shiqing; Hu, Han; Wu, Jinzhe; Li, Xuewen; Ma, Xinying; Zhao, Zhezhe; Liu, Zihao; Wu, Chenxuan; Zhao, Bo; Wang, Yonglan; Jing, Wei
Abstract: Objectives: Diabetic wound healing remains a global challenge in the clinic and in research. However, the current medical dressings are difficult to meet the demands. The primary goal of this study was to fabricate a functional hydrogel wound dressing that can provide an appropriate microenvironment and supplementation with growth factors to promote skin regeneration and functional restoration in diabetic wounds. Materials and Methods: Small extracellular vesicles (sEVs) were bound to the porcine small intestinal submucosa‐based hydrogel material through peptides (SC‐Ps‐sEVs) to increase the content and achieve a sustained release. NIH3T3 cell was used to evaluate the biocompatibility and the promoting proliferation, migration and adhesion abilities of the SC‐Ps‐sEVs. EA.hy926 cell was used to evaluate the stimulating angiogenesis of SC‐Ps‐sEVs. The diabetic wound model was used to investigate the function/role of SC‐Ps‐sEVs hydrogel in promoting wound healing. Results: A functional hydrogel wound dressing with good mechanical properties, excellent biocompatibility and superior stimulating angiogenesis capacity was designed and facilely fabricated, which could effectively enable full‐thickness skin wounds healing in diabetic rat model. Conclusions: This work led to the development of SIS, which shows an unprecedented combination of mechanical, biological and wound healing properties. This functional hydrogel wound dressing may find broad utility in the field of regenerative medicine and may be similarly useful in the treatment of wounds in epithelial tissues, such as the intestine, lung and liver. Abstract : Schematic illustration showing synthesis of the SC‐Ps scaffold dressing and nanoscale sEVs loaded SC‐Ps scaffold dressing and the potential application of the dressings in diabetic wound healing and skin reconstruction.